Clinical Significance of Baseline Neutrophil-to-Lymphocyte Ratio in Patients With Ischemic Stroke or Hemorrhagic Stroke: An Updated Meta-Analysis - Song, Si-Ying; Zhao, Xiao-Xi; Rajah, Gary; Hua, Chang; Kang, Rui-jun; Han, Yi-peng; Ding, Yu-chuan; Meng, Ran (Frontiers in Neurology, 2019)
Background and purpose: Study on the relationship between baseline neutrophil to lymphocyte ratio (NLR) and stroke, and analyze the prognostic value of NLR in subtypes of stroke. Methods: This meta-analysis was registered in PROSPERO with the number CRD42018105305. We went through relevant articles from PubMed Central (PMC) and EMBASE, included either prospective or retrospective studies about baseline NLR level before any treatment in patients with ischemic or hemorrhagic stroke, to identify studies up to April 2019. The cut-off value for NLR and the sources of ORs/RRs were measured. Modified Rankin Scale (mRS) was used to investigate the outcomes during clinical follow-up. Predefined criteria were used to evaluate the risk of bias in eligible studies. P-values < 0.05 were considered statistically significant. STATA version 14.0 (STATA, College Station, TX) was used in all analyses. Results: 37 studies with 43,979 individuals were included in the final analysis. Higher NLR level was corelated with increased risk of ischemic stroke (ORs/RRs = 1.609; 95% CI = 1.283 - 2.019), unfavorable functional outcome at 3 months (ORs/RRs = 1.851; 95% CI = 1.325 - 2.584) and increased mortality in patients with ischemic stroke (ORs/RRs = 1.068; 95% CI = 1.027 - 1.111). While in terms of hemorrhagic stroke (including SAH and ICH), elevated NLR level only had deleterious effect on mortality (ORs/RRs = 1.080; 95% CI = 1.018 - 1.146). Conclusions: Baseline NLR level is a promising predictor of the clinical outcomes in both ischemic and hemorrhagic stroke. In addition, elevated NLR is also associated with a high risk of ischemic stroke occurrence. However, future studies are needed to demonstrate the underlying mechanisms.